2009
DOI: 10.1186/1471-244x-9-11
|View full text |Cite
|
Sign up to set email alerts
|

The response of mental health professionals to clients seeking help to change or redirect same-sex sexual orientation

Abstract: Background: we know very little about mental health practitioners' views on treatments to change sexual orientation. Our aim was to survey a representative sample of professional members of the main United Kingdom psychotherapy and psychiatric organisations about their views and practices concerning such treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 16 publications
2
54
0
4
Order By: Relevance
“…Currently, a significant minority of mental health professionals continues to offer hope for sexual reorientation (Bartlett, Smith, & King, 2009). Those who promote such changes tend to believe homosexuality is a learned behavior.…”
Section: The History Of Trying To Change Homosexualsmentioning
confidence: 98%
“…Currently, a significant minority of mental health professionals continues to offer hope for sexual reorientation (Bartlett, Smith, & King, 2009). Those who promote such changes tend to believe homosexuality is a learned behavior.…”
Section: The History Of Trying To Change Homosexualsmentioning
confidence: 98%
“…Nonetheless, the practice of and advocacy for SOCE continues (Drescher 2003, pp. 431-32;Bartlett et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…However four participants said that sexual orientation was made part of the agenda by the counsellor rather than themselves and seven felt the counsellor over-focused on this. In relation to Bartlett et al, (2009) research, two participants reported that they were offered 'conversion therapy' by their counsellors. Burke (1989) states that it is important for counsellors to know when sexual orientation is the focus of counselling and when it is not, and it appears that a minority of counsellors, from the client's perspective, still showed lack of sensitivity in this area.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, King and McKeown found that a third of gay men, a quarter of bi men and over 40% of lesbian women had negative or mixed reactions from mental health professionals when being open about their sexuality (DOH, 2006). More recently, research found that 17% of therapists had, in the past, attempted to assist their clients to reduce their 'homosexual feelings' with 4% reporting that they would still attempt to change their client's sexual orientation (Bartlett et al, 2009). This study was taken up by the mass media in an unprecedented way, suggesting that concerns with LGB counselling have reached the point of public interest.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation